An instant beverage rich in nutrients and secondary metabolites manufactured from stems and leaves of Panax notoginseng - Liang, Zhengwei; Liu, Kunyi; Li, Ruoyu; Ma, Baiping; Zheng, Wei; Yang, Shengchao; Zhang, Guanghui; Zhao, Yinhe; Chen, Junwen; Zhao, Ming (Frontiers in Nutrition, 2022)
Radix Notoginseng, one of the most famous Chinese traditional medicines, is the dried root of Panax notoginseng (Araliaceae). Stems and leaves of P. notoginseng (SLPN) are rich in secondary metabolites and nutrients, and authorized as a food resource, however its utilization needs further research. In this study, a SLPN-instant beverage, with extraction rate of 37.89 ± 0.02% was manufactured through optimization by response surface design, which were as follow: SLPN extracted with 21-fold of 48.50% ethanol for 39 h, and this extraction was repeated twice; the extraction solution was concentrated to 1/3 volume using a vacuum rotatory evaporator at 45°C, and then spray dried at 110°C. Nutritional components including 14 amino acids, ten mineral elements, 15 vitamins were detected in the SLPN-instant beverage, and majority were Gly (2.10 ± 0.63 mg/g), His (1.23 ± 0.07 mg/g), α-VE (18.89 ± 1.87 μg/g), β-VE (17.53 ± 1.98 μg/g), potassium (49.26 ± 2.70 mg/g), calcium (6.73 ± 0.27 mg/g). Forty-three triterpenoid saponins, e.g., ginsenoside La, ginsenoside Rb3, notoginsenoside R1, and two flavonoid glycosides, as well as dencichine were identified by UPLC-MS. The total saponin of the SLPN-instant beverage was 403.05 ± 34.98 mg/g, majority was notoginsenoside Fd and with contents of 227. In addition, catechin and γ-aminobutyric acid were detected with levels of 24.57 ± 0.21 mg/g and 7.50 ± 1.85 mg/g, respectively. The SLPN-instant beverage showed good antioxidant activities with half maximal inhibitory concentration (IC50) for scavenging hydroxyl (OH-) radicals, superoxide anion (O2-) radicals, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS+) radicals were 0.1954, 0.2314, 0.4083 and 0.3874 mg/mL, respectively. Finally, we optimized an analytical method for in depth analysis of the newly authorized food resource SLPN. Together, an instant beverage with antioxidant activity, rich in nutrients and secondary metabolites, was manufactured from SLPN, which may improve the utilization of SLPN.